Energy-Aware Wireless Sensor Networks MAC Modelling and Simulation with Efficient Transceivers - Barroca, Norberto (2010)
This paper addresses an analytical model that may be applied to different Wireless Sensor Networks (WSNs) Medium Access Control (MAC) protocols using different efficient transceivers. Our model accounts for the impact of several simultaneous factors, including periodic receive/transmit and sleep cycles, the length of the transmitted packet and data rate. The Sensor Block Acknowledgement MAC, a new innovative WSNs MAC protocol that uses a Block Acknowledgement scheme to achieve energy efficiency, is proposed as well. Our implementation takes into account the average delay, which can be clearly reduced when a Block Acknowledgement Scheme is used. In terms of energy consumption and average delay the efficient radio transceivers that operate in the 2.4GHz band have better results that the ones that use the 900MHz band. Adaptive listening (AL) enables radio transceivers to stay alert after the communication between two neighbour nodes before going to sleep, allowing for energy saving when synchronisation is involved.